Frailty and Mortality Risk Among Dogs with Extreme Longevity: Development and Predictive Validity of a Clinical Frailty Index in the Exceptional Aging in Rottweilers Study - David J. Waters; Aimee H. Maras; Rong Fu; Andres E. Carrillo; Emily C. Chiang; Cheri L. Suckow (Animals)
Frailty refers to a state of increased vulnerability to mortality and other adverse outcomes as a consequence of age-related decline in physiologic reserve and function. Comparative biomedical scientists are relied upon to innovate approaches to enhance understanding of the similarities and differences between humans and other animal species that can impact healthy aging. The research aim of this study was to develop a clinical frailty index (FI) in the Exceptional Aging in Rottweilers Study (EARS) and test its ability to predict all-cause mortality in elderly dogs. EARS is an ongoing lifetime cohort study of pet dogs with extreme longevity living in North America. Living 30% longer than the breed average, these dogs represent the canine counterpart to human centenarians. A 34-item FI (EARS-FI) was constructed to assess deficit accumulation using clinical data collected by telephone interviews with owners of 93 dogs with extreme longevity. Health deficits across multiple domains, including cognitive and sensory, cardiovascular and endocrine, and mobility, were included. The association between EARS-FI and subsequent mortality was tested in Kaplan-Meier survival analysis and in age-adjusted Cox proportional hazard models. Median (interquartile range) EARS-FI was 0.43 (0.38–0.50), and the estimated frailty limit was 0.68, consistent with data reported in humans with extreme longevity. Frailty index increased with increasing chronological age (p < 0.001). Deficit accumulation was significantly associated with increased mortality risk. Age-adjusted hazard ratio for mortality per 0.01 unit increase in FI was 1.05 (95%CI, 1.02–1.08; p = 0.001). This work provides the first demonstration of a strong association between frailty and mortality risk in pet dogs with extreme longevity. Notably, EARS-FI showed key features observed in the evaluation of frailty in aging human populations: heterogeneity, increase with chronological age, and estimated limit of <0.7. Validated here as a predictor of mortality in aged pet dogs, EARS-FI offers a useful tool for further comparative analyses of the linkages between deficit accumulation, mortality, and other adverse health outcomes.